The Development of Authentic Assessment Instrument to Expand the Character Values of CitizenshipEducation at Primary School No 104202 and No 106811 Bandar Setia, Medan, Indonesia - Deny Setiawan (BIRCU, 2019)
This developmental research aims to produce an authentic assessment instrument in the domain of skills to develop the character values of citizenship. The subjects of this research are: (1) Primary School teachers; (2) Primary School students; (3) Eight experts for validation of assessment instruments that is the validation experts of mathematics for Primary Schools, Natural Science for Primary School, Social Sciences for Primary School, Bahasa Indonesia, Civics for Primary School, Assessment, Psychology, and Character Education. The method used in this research is a developmental research method of formative research type which in its development is focused on 2 stages that is preliminary stage and formative evaluation stage. The data were collected through questionnaires and field tests. The results of field tests (small and large scale) show that the eveloped authentic assessment instruments have excellent validity and high reliability. Thus, based on the results of validation expert and field tests, it can be concluded that the authentic assessment instruments have been valid and have a category of reliability which is very high, so the instrument is worthy to develop the character values of citizenship.